PEMBATALAN PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN MELALUI PENGADILAN NEGERI - Darwis Manurung (JURNAL AKTA YUDISIA, 2020)
Abstract Litigation dispute resolution is the settlement of a dispute through a court which results in a win and lose decision. The decision gives the one party wins and the other party loses. Non-litigation dispute resolution is the settlement of a dispute outside the court where it produces a win-win solution.Based on the Decree of the Minister of Industry and Trade of the Republic of Indonesia Number: 350 / MPP / Kep / 12/2001 concerning Implementation of Duties and Authorities of the Consumer Dispute Settlement Agency Article 3 Letter a states that the dispute resolution process in BPSK can be pursued in three ways, namely by means of Conciliation, Mediation or Arbitration. Through these three ways of resolving it is expected to produce a decision that provides a win-win solution for the parties. However, it is inevitable that in reality not all decisions made by BPSK with this arbitration will give satisfaction to the parties.The purpose of writing this paper is to find out the authority of the District Court to cancel the BPSK Decision and also know how to file an objection to the BPSK Decision.The authority of the District Court to cancel the BPSK Arbitration verdict is based on Article 58 UUPK and Article 41 paragraph (3) Decree of the Minister of Industry and Trade of the Republic of Indonesia Number 350 / MPP / Kep / 12/2001.